Stability Performance of a Quantum Square-shaped Extended Source P-N-P-N TFET with Silicon Carbide Substrate by Means of a Physics-Based Analytical Model - Sabaghi, Masoud (TECCIENCIA, 2020)
In this paper, an analytical stability model for quantum square-shaped extended source P-N-P-N tunneling field-effect transistor (P-N-P-N TFET) with silicon carbide substrate is developed that includes the effects of gate-source capacitance, gate-drain capacitance, effective gate resistance, time constant and transconductance. A nonquasistatic RF small-signal model has been used and stability that was extracted from analytical equations of its Y-parameters. The obtained analytical expression for stability is compared with device simulation results and excellent agreement is found up to 100 GHz. The stability performance of a quantum square-shaped extended source P-N-P-N TFET with silicon carbide substrate is also studied analytically considering pocket width and doping variation. The results strongly confirm that the proposed model is accurate and suitable for the quantum square-shaped extended source P-N-P-N TFET in the high-frequency regime.